Representação da imagem do medo em crianças de 6 a 11 anos - Nasi, Maria Teresa Corbucci Caldeira (2016)
The aim of this work is to study how fear evolves through development on 6 to 11 years old children from an Analytical Psychology theoretical perspective. This work surveys the symbols generated by the psyche of children on the different expressions of fear. The participants were 198 children from schools located in the city of São Paulo. The instrument used in the data collection was a drawing, requested to the children with the question: "What makes you feel fear?". Upon receipt of the drawing, the following question was made: "What did you draw and why does it make you feel fear?". The drawings were studied with respect to the children's development, gender, age, social environment and type of school (public or private). This work is characterized as a survey of a quantitative nature, out of which three distinct classes for analysis were established: Creatures and Real Situations, Fantastic and Supernatural Creatures and Imaginary and Future Projections. The collected data were subject to a symbolic analysis through Jung´s symbolic amplification constructive method. Results indicate that fears appear on a distinct manner, varying according to gender, age and type of school. In the classes Creatures and Real Situations and Fantastic and Supernatural Creatures, a decrease in the number of drawings was observed according to the respective age. However, in the Imaginary and Future Projections class, children increase the number of drawings